New syngeneic inflammatory‐related lung cancer metastatic model harboring double KRAS/WWOX alterations. Issue 11 (28th January 2014) - Bleau, Anne‐Marie; Freire, Javier; Pajares, María José; Zudaire, Isabel; Anton, Iker; Nistal‐Villán, Estanislao; Redrado, Miriam; Zandueta, Caroli na; Garmendia, Irati; Ajona, Daniel; Blanco, David; Pio, Ruben; et al.
Abstract : New mouse models with specific drivers of genetic alterations are needed for preclinical studies. Herein, we created and characterized at the genetic level a new syngeneic model for lung cancer and metastasis in Balb‐c mice. Tumor cell lines were obtained from a silica‐mediated airway chronic inflammation that promotes tumorigenesis when combined with low doses of N ‐nitrosodimethylamine, a tobacco smoke carcinogen. Orthotopic transplantation of these cells induced lung adenocarcinomas, and their intracardiac injection led to prominent colonization of various organs (bone, lung, liver and brain). Driver gene alterations included a mutation in the codon 12 of KRAS (G–A transition), accompanied by a homozygous deletion of the WW domain‐containing oxidoreductase ( WWOX ) gene. The mutant form of WWOX lacked exons 5–8 and displayed reduced protein expression level and activity. WWOX gene restoration decreased the in vitro and in vivo tumorigenicity, confirming the tumor suppressor function of this gene in this particular model. Interestingly, we found that cells displayed remarkable sphere formation ability with expression of specific lung cancer stem cell markers. Study of non‐small‐cell lung cancer patient cohorts demonstrated a deletion of WWOX in 30% of cases, with significant reduction in protein levels as compared to normal tissues. Overall, our new syngeneic mouse model provides a most valuable tool to study lung cancer metastasis in balb‐c mice background and highlights the importance of WWOX deletion in lung carcinogenesis. Abstract : What's new? Cell and animal models are essential for understanding the drivers of genetic alterations in cancer, though new mouse models for pre‐clinical investigation are needed. The present report describes a novel mouse model for lung cancer that was established with metastatic lung tumor cells from mice that carry two driver gene alterations: a mutation in KRAS and a homozygous deletion in WWOX (WW domain‐containing oxidoreductase). WWOX deletion was found in 30% of non‐small cell lung cancer patients. Functional analyses confirmed a tumor suppressor role for WWOX, supporting its relevance in lung tumor progression and invasion.